4(n+6)-2n=3(n+3)-11

Simple and best practice solution for 4(n+6)-2n=3(n+3)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n+6)-2n=3(n+3)-11 equation:


Simplifying
4(n + 6) + -2n = 3(n + 3) + -11

Reorder the terms:
4(6 + n) + -2n = 3(n + 3) + -11
(6 * 4 + n * 4) + -2n = 3(n + 3) + -11
(24 + 4n) + -2n = 3(n + 3) + -11

Combine like terms: 4n + -2n = 2n
24 + 2n = 3(n + 3) + -11

Reorder the terms:
24 + 2n = 3(3 + n) + -11
24 + 2n = (3 * 3 + n * 3) + -11
24 + 2n = (9 + 3n) + -11

Reorder the terms:
24 + 2n = 9 + -11 + 3n

Combine like terms: 9 + -11 = -2
24 + 2n = -2 + 3n

Solving
24 + 2n = -2 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
24 + 2n + -3n = -2 + 3n + -3n

Combine like terms: 2n + -3n = -1n
24 + -1n = -2 + 3n + -3n

Combine like terms: 3n + -3n = 0
24 + -1n = -2 + 0
24 + -1n = -2

Add '-24' to each side of the equation.
24 + -24 + -1n = -2 + -24

Combine like terms: 24 + -24 = 0
0 + -1n = -2 + -24
-1n = -2 + -24

Combine like terms: -2 + -24 = -26
-1n = -26

Divide each side by '-1'.
n = 26

Simplifying
n = 26

See similar equations:

| 7+30x=20x+23 | | 5*(4-9*2)-2*(3*2+4)+7= | | 3w^6*v^9*2v^4*7w=0 | | 32=X-5 | | y=0.5+-1.5y+1 | | 64=l-4 | | 3w^6*v^8*2v^4*7w=0 | | 40/(-5) | | 250=9x-38 | | 6z-30= | | 21x^2+50xy-16y^2=0 | | -0.8n=40 | | Z/3=z—2 | | Y(x+1)-4(x+1)= | | -.125c=2 | | x+2x+3x+4=40 | | 16x=256/x | | 8-3x+7x=-12 | | 4x+40+3x=180 | | m=-1/2;(-4,7) | | (3-u)(3u-2)=0 | | 9ln(x+18)-6ln(x)= | | y=4(0.5) | | -(4y-5)(5y-8)= | | X^2+3x=49 | | 6x^4+40x^3y-14x^2y^2=0 | | 21-4x=12-7x | | 15x=121 | | 2*1/3 | | x-10-4x=-25 | | 3+10+5y=20 | | 3x=2+1 |

Equations solver categories